Math, asked by yashsharmackt, 1 year ago

pls solve it

you have to prove the identity
R.H.S. =L.H.S.
correct answer will be brainlist ​

Attachments:

Answers

Answered by MOSFET01
6

Solution

In above attachment answer is attached

Take LHS

\implies (1 + tan A + cot A)(sin A - cos A)

\implies sin A - cos A + tan A.sin A + cot A.sin A - tan A.cos A - cot A. cos A

\implies sin\: A \: - \: cos\: A\: +\dfrac{sin\: A}{cos\: A}. sin \: A \: +\: \dfrac{cos\: A}{sin\: A}. sin\:A\: - \:\dfrac{sin\:A}{cos\:A}. cos\:A \: - \:\dfrac{cos\: A}{sin\:A}. cos\: A

Eliminate same value

\implies sin\: A \:-\: cos \: A \:+\:\dfrac{sin^{2}\:A}{cos\:A}\: + \:cos \: A \: - \:sin\:A\:-\:\dfrac{cos^{2}\:A}{sin\:A}

\implies \dfrac{sin^{2}\:A}{cos\:A}\:-\:\dfrac{cos^{2}\:A}{sin\:A}

\implies sin\:A.tan\:A\:-\: cot\:A.cos\:A

 \boxed{L.H.S\: =\: R.H.S}

Hence proved

Attachments:
Similar questions